Safety and effectiveness of gemcitabine for the treatment of classic Kaposi's sarcoma without visceral involvement. (March 2022) - Badalamenti, Giuseppe; Incorvaia, Lorena; Algeri, Laura; Bonasera, Annalisa; Dimino, Alessandra; Scalia, Raimondo; Cucinella, Alessandra; Madonia, Giorgio; Pomi, Federica Li; Galvano, Antonio; Gristina, Valerio; Toia, Francesca; et al.
Background: Classic Kaposi's sarcoma (CKS) is a rare, multifocal, endothelial cell neoplasm that typically occurs in elderly people with previous infection by human herpes virus-8. Prospective trials are rare, and the choice of drugs relies on prospective trials performed on HIV-associated Kaposi's sarcoma (KS). Pegylated liposomal anthracyclines and taxanes are considered the standard first- and second-line chemotherapy, respectively. Despite the indolent biologic behavior, the natural history is characterized by recurrent disease. This condition of chronic administration of cytotoxic drugs is often associated with immediate/long-term adverse events. Methods: This was an observational, retrospective study to evaluate the effectiveness and safety of gemcitabine in patients with CKS. From January 2016 to September 2021, the patients were treated with gemcitabine 1000 mg/m 2 on days 1 and 8, with cycles repeated every 21 days. The treatment was administered as first or second line. Results: Twenty-seven (27) patients were included in the study. Twenty-one (21) out 27 patients (77.8%) achieved a partial response (PR), including 8 patients with major response (MR) (29.6%) and 13 patients with minor response (mR) (48.2%); 2 (7.4%) showed a complete response (CR), 3 (11.1%) a stable disease (SD), and 1 (3.7%) a progressive disease (PD). Tumor responses were generally rapid, with a median time to first response of 4 weeks (range, 3–12 weeks). Patients who responded had disease improvement with flattening of the skin lesions, decrease in the number of lesions, and substantial reduction in tumor-associated complications. Median duration of response was 19.2 months. Common adverse events were grades 1/2 thrombocytopenia, and grade 1 noninfectious fever. No patient discontinued treatment as a result of adverse events. Conclusion: Our study showed that gemcitabine is effective and well tolerated, acts rapidly on cutaneous lesions, and allows substantial symptom palliation, without dose-limiting toxicity. Gemcitabine represents a safe and effective option for the treatment of CKS.